Library Assistant - improving the student experience of Oxford libraries through a mobile library induction - Bridle, O; Carritt, A (2014)
A student’s first week at University is an overwhelming experience with important information being delivered by many different parts of the institution. High student numbers and severe time constraints on contact time between librarians and students means that libraries struggle to effectively communicate advice about services and resources. This issue is further compounded at the University of Oxford by the complexity of the local library system; the second largest in the UK. Research undertaken with Oxford students to ascertain their views on library inductions revealed that, although inductions were valued, they could be poorly timed and leave students overloaded with information they subsequently failed to retain. It was decided that a mobile-friendly website which provided key information about libraries in Oxford could address these difficulties by enabling students to get timely access to concise information using smartphones and tablet devices. The aim was to encourage students to use the library and ensure that they get the maximum benefit from library resources across the institution during their studies. Funding from JISC allowed the development and rollout of the ‘Library Assistant for Oxford Freshers’ website. This paper discusses the motivations for creating Library Assistant, how the website was developed and what the response has been from new library users. This paper shows that Library Assistant provides an example of how libraries can exploit mobile technology to enhance the patron experience and use of library services.